2008
DOI: 10.3155/1047-3289.58.11.1434
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Odor, Ammonia, Hydrogen Sulfide, and Carbon Dioxide Emission Profiles of Confined Swine Grower/Finisher Rooms

Abstract: The objective of this study was to obtain diurnal variation profiles of odor and gas (ammonia [NH3], hydrogen sulfide [H2S], carbon dioxide [CO2]) concentrations and emission rate (OGCER) from confined swine grower/ finisher rooms under three typical weather conditions (warm, mild, and cold weather) in a year. Two grower/ finisher rooms, one with a fully slatted floor and the other with partially slatted floors, were measured for 2 consecutive days under each weather condition. The results revealed that the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 11 publications
1
36
0
1
Order By: Relevance
“…The reason could be due to low correlations between odor and NH 3 and H 2 S concentrations. 15 Overall, the general seasonal H 2 S pattern indicated that higher manure and room temperatures in the warm season considerably favored H 2 S production in the rooms. Because of the high ventilation rate and high H 2 S concentration in the warm season, the H 2 S emission rates were high in the warm season and low in the cold season.…”
Section: Ppm Except For Two Peaks Occurring In October 2004mentioning
confidence: 89%
See 2 more Smart Citations
“…The reason could be due to low correlations between odor and NH 3 and H 2 S concentrations. 15 Overall, the general seasonal H 2 S pattern indicated that higher manure and room temperatures in the warm season considerably favored H 2 S production in the rooms. Because of the high ventilation rate and high H 2 S concentration in the warm season, the H 2 S emission rates were high in the warm season and low in the cold season.…”
Section: Ppm Except For Two Peaks Occurring In October 2004mentioning
confidence: 89%
“…Odor and gas emission rates were determined by multiplying the increase in odor and gas concentrations between the room ventilation outlet and inlet by the total airflow rate of the exhaust fans, expressed in OU AU Ϫ1 sec Ϫ1 for odor, or mg AU Ϫ1 sec Ϫ1 for gas (1 animal unit [AU] ϭ 500 kg of animal mass). The detailed method of the odor and gas measurements in this study was presented in Sun et al 15 It should be noted that the uncertainty of emission rate calculations is primarily associated with the uncertainty in barn ventilation rate measurement because of various factors; for example, dust accumulation on fan shutters and blades, loose fan belts, changes in building static pressure, and changes of power supply to the fans all affect the ventilation rate. Thus, the fan performance in the field might be different from the laboratory testing results.…”
Section: Experiments Design and Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in CO 2 and CH 4 flux from SBP treatment is small when put into the context of total GHG emissions from a US commercial swine finisher and swine gestation barn with a deep pit storage. The increase in CO 2 as a result of the SBP/CaO 2 treatments of 2.28, 4.57, 22.8 and 45.7 kg/m 2 equates to 0.52e0.68, 0.66e0.86, 2.01e2.62, and 2.97e3.88% of the total CO 2 emitted from a typical swine finisher with deep pit, respectively (Sun et al, 2008;Ni et al, 2008). There is much greater CO 2 contribution from pigs' respiration, combustion from natural gas-fired space heaters, and from microbial activity in manure.…”
Section: Treatment Effects On Greenhouse Gasesmentioning
confidence: 94%
“…Indeed with a partly-slatted floor, the fouling of the solid floor can be important, especially in case of summer conditions and high animal density (European Commission, 2003;Aarnink et al, 2006). So, if some of the authors observed a decrease of NH 3 -emissions with the use of a partly-slatted floor compared to a fully-slatted floor with fattening pigs (Groot Koerkamp et al, 1998;Sun et al, 2008;Ye et al, 2009), some others observed similar or increased NH 3 -emissions (Guingand and Granier, 2001;Guingand and Courboulay, 2007;Guingand et al, 2010). In addition in the current study, the clogging of the holes with animal waste in the R2.5 room could impair the drainage properties of the solid part of the floor with negative impact on NH 3 -emissions.…”
Section: Discussionmentioning
confidence: 99%